3D Bioprinting of Cartilage for Orthopedic Surgeons: Reading between the Lines - Di Bella, Claudia; Fosang, Amanda; Donati, Davide M.; Wallace, Gordon G.; Choong, Peter F. M. (Frontiers in Surgery, 2015)
Chondral and Osteochondral lesions represent one of the most challenging and frustrating scenarios for the orthopaedic surgeon and for the patient. The lack of therapeutic strategies capable to reconstitute the function and structure of hyaline cartilage and to halt the progression towards osteoarthritis has brought clinicians and scientists together, to investigate the potential role of tissue engineering as a viable alternative to current treatment modalities. In particular, the role of bioprinting is emerging as an innovative technology that allows for the creation of organized 3D tissue constructs via a “layer-by-layer” deposition process. This process also has the capability to combine cells and biomaterials in an ordered and predetermined way. Here we review the recent advances in cartilage bioprinting and we identify the current challenges and the directions for future developments in cartilage regeneration.